Salivary and Serum Antioxidant Activity in Patients with Acute Coronary Syndrome - Y, Gulati; VS, Narain; AK, Saxena; PK, Nigam; B, Ali (IIUM Medical Journal Malaysia, 2012)
Introduction: Oxidative stress has been implicated in the pathogenesis of many diseases, including cardiovascular diseases. However, much less is understood about the redox status of patients with acute coronary syndrome (ACS). The present study was, therefore, designed to evaluate the redox status of patients with ACS prior to and following therapy as compared to age-matched healthy individuals by monitoring the antioxidant potential of serum and saliva as biomarkers of oxidative stress and evaluating their likely correlation with the clinical status of the patients. Methods: A total of 33 patients (29-78 year old, male) with the diagnosis of ACS and age-matched 16 healthy male (control) were included in the study. The diagnosis of ACS was based on the clinical presentation, ECG and serum cardiac biomarkers. These patients were grouped as acute myocardial infarction with ST-segment elevation subtype (STEMI, n=24) and non-ST-segment elevation myocardial infarction subtype (NSTEMI, n=9). Serum and salivary antioxidant activity (AOA) were determined spectrophotometrically. Results: Antioxidant defense, as reflected by lower total AOA in saliva and serum, was found to be significantly attenuated in patients with ACS as compared to control subjects, indicating an increased oxidative stress. The decrease in AOA was more conspicuous in patients with STEMI as compared to non-NSTEMI suggesting more oxidative stress in the former is associated with the severity of the disease, including tissue necrosis in STEMI patients. Drug treatment to ACS patients for a short-term period (4-6 days) elicited no significant improvement in their AOA. However, ACS patients receiving longterm drug treatment (4-5 weeks) exhibited a significant increase in AOA as well as an improvement in the clinical status. Conclusion: This preliminary study supports the role of oxidative stress in the pathogenesis of ACS and the use of salivary and serum AOA as a potential marker of the redox status and disease severity.